Optimalisasi Pertumbuhan dan Hasil Bawang Merah (Peran Komposisi Media Tanam dan Konsentrasi Pupuk Organik) - Ayu Regita Cahyati; Rusmana Rusmana; Endang Sulistyorini; Dewi Firnia (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Shallots (Allium ascalonicum L.) are horticultural products that are highly sought after because they are often used for various purposes. However, the high demand for this product is not matched by its production levels. The excessive use of chemical products can reduce the nutrient content in the soil, making it difficult to achieve maximum production yields. The solution that can be implemented to solve the problem is to add organic materials to the cultivation process. This research investigated the combined effect of media composition and liquid organic fertilizer (LOF) on the growth and yield of shallots. This research is located at the Integrated Agricultural System Area in Curug District, Serang City, Banten, from May to August 2024. This experimental research uses a Randomized Block Design with two factors and three replications, resulting in 36 experimental units where each experimental unit contains two plants, totaling 72 plants. The first factor is the composition of the planting media soil: husk charcoal: cow manure fertilizer, which consists of 4 ratios: (1:1:1), (2:1:1), (1:2:1), and (1:1:2). The second factor is the concentration of GDM LOF, which consists of 3 levels: 6 mL/L, 8 mL/L, and 10 mL/L. The research results show that the treatment of planting media composition significantly affects plant height and number of leaves, with the best treatment being the planting media composition of soil: husk charcoal: cow manure fertilizer (1:2:1). Meanwhile, the treatment of GDM LOF concentration significantly effects on plant height, number of leaves, and tuber diameter, with the best treatment being the GDM LOF concentration of 8 mL/L. Interaction was found in plant height at 2 weeks after planting.